Evaluation of herb-drug interaction of ambrisentan with shikonin based on UPLC-MS/MS. (1st January 2021) - Lan, Tian; Fang, Ping; Ye, Xuemei; Lan, Xia; Xu, Ren-ai
Abstract: Context: Ambrisentan is an oral endothelin-receptor antagonist (ERA). However, there is no report on the interaction between ambrisentan and shikonin. Objective: To investigate the effect of shikonin on ambrisentan metabolism in vivo and in vitro . Materials and methods: This study developed an ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method for simultaneous determination of ambrisentan and ( S )-4-hydroxymethyl ambrisentan in rat plasma. Twelve male Sprague-Dawley (SD) rats were divided into two groups ( n  = 6): the control group and shikonin (20 mg/kg) group. The pharmacokinetics of ambrisentan (2.5 mg/kg) were investigated after 30 min. Additionally, human and rat liver microsomes were used to investigate the herb-drug interaction. Results: The UPLC-MS/MS method was shown to be accurate, precise and reliable, and was successfully applied to the herb-drug interaction study of ambrisentan with shikonin. When co-administrated with 20 mg/kg shikonin, the C max and AUC(0–∞) of ambrisentan were significantly increased by 44.96 and 16.65%, respectively ( p  < 0.05). In addition, there were modest decreases in ( S )-4-hydroxymethyl ambrisentan Cmax and AUC(0–∞) in the presence of shikonin ( p  < 0.05), which indicated that these results were in accordance with the inhibition of shikonin on ambrisentan metabolism. Moreover, enzyme kinetic study indicated that shikonin had an inhibitory effect on human and rat microsomes where the IC50 values of shikonin were 5.865 and 6.358 μM, respectively. Conclusions: Our study indicated that shikonin could inhibit ambrisentan metabolism. Further studies need to be carried out to verify whether similar interaction truly apply in humans and whether this interaction has clinical significance.